New directions in entrepreneurial finance - Cumming, Douglas; Deloof, Marc; Manigart, Sophie; Wright, Mike (Journal of Banking & Finance, 2019)
Entrepreneurial finance is a distinctive aspect of corporate finance, notably with respect to informational asymmetries and investor involvement in portfolio companies. Entrepreneurial finance research has explored four levels of analysis: the entrepreneur or entrepreneurial firm, the organization providing finance to the entrepreneurs, the organizations providing funds to these organizations, and the region or country in which the entrepreneurial firms or investors are established. We discuss recent developments in forms of entrepreneurial finance. We summarize the contributions of the papers published in this issue on entrepreneurial finance at different points in the life cycle, including work on trade credit, debt finance, micro-cap IPOs, venture capital, and angel finance. Also, we highlight avenues for future research focusing on funding gaps, accelerators, crowdfunding, secondary buyouts, boards, and exits.